Aplikasi Knowledge Management Metrics pada Perancangan Dashboard KMS untuk Monitoring Strategi (Studi Kasus: Fakultas Sains dan Teknologi UIN Suska Riau) - Okfalisa Okfalisa; Dayub Dayub (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2015)
The successful of strategy execution in an organization is essential. Many models have been used to measure the successful achievement of its strategy including Knowledge Management Metrics (KMM) application. KMM as one of performance measurement tools is eligible in measuring the successful level of strategy execution based on the involvement of top and middle managers as a key success factor in this execution. In order to automate the achievement of measurement, a Knowledge Management System (KMS) in terms of dashboard model is built to monitor and evaluate the process. Based on Top and Middle managers answers in this system, KMS provides any information regarding on the speed of strategy execution achievement within speedometer performance layout, any obstacles assumptions facing, any changes assumptions and recommendations as corrective actions towards the successful achievement are also presenting in this system. This Dashboard KMS-Web speedometer can aid management level in making decisions and producing policy related to strategy execution performance. The emergence of negative risk can be detected, the caused and effect which related to management or organization can be minimized.Keywords: Dashboard Model, Knowladge Management System, Monitoring, Strategy Achievement, Strategy Execution, Web-Speedometer.